Circulating testosterone as the hormonal basis of sex differences in athletic performance - Handelsman, D. J.; Lindén Hirschberg, A.; Bermon, S. (Endocrine Reviews, 2018)
Elite athletic competitions have separate male and female events due to men`s physical advantages in strength, speed and endurance so that a protected female category with objective entry criteria is required. Prior to puberty, there is no sex difference in circulating testosterone concentrations or athletic performance but from puberty onwards sex difference in athletic performance emerges as circulating testosterone concentrations rise in men because testes produce 30 times more testosterone than before puberty with circulating testosterone exceeding 15-fold those of women at any age. There is a wide sex difference in circulating testosterone concentrations and reproducible dose-response relationship between circulating testosterone and muscle mass and strength as well as circulating hemoglobin in both men and women. These dichotomies largely accounts for the sex differences in muscle mass and strength and circulating hemoglobin levels resulting in at least an 8-12% ergogenic advantage in men. Suppression of elevated circulating testosterone of hyperandrogenic athletes results in negative effects on performance, which are reversed when suppression ceases. Based on the non-overlapping, bimodal distribution of circulating testosterone concentration (measured by liquid chromatography-mass spectrometry) and making allowance for women with mild hyperandrogenism including that of polycystic ovarian syndrome, who are over-represented in elite athletics, the appropriate eligibility criterion for female athletic events should be a circulating testosterone of less than 5.0 nmol/L. This would include all women other than those with untreated hyperandrogenic disorders of sexual development (DSD), testosterone-treated female-to-male (F2M) transgender, noncompliant male-to-female (M2F) transgender or androgen doping.